The Routledge Handbook of Global Islam and Consumer Culture - A Hashfi Luthfi (UIN Sunan Kalijaga Yogyakarta, 2025)
The Routledge Handbook of Global Islam and Consumer Culture, edited by Birgit Krawietz and François Gauthier, offers a comprehensive examination of the intersection between Islam, market dynamics, and consumer practices in the contemporary global era. The book’s interdisciplinary contributions demonstrate how Islamic values, authority, and socio-economic realities shape consumer culture across diverse contexts. By bringing together perspectives from law, anthropology, sociology, and religious studies, the volume examines critical themes such as halal markets, financial ethics, identity politics, and digital consumption. This review highlights the book’s strength in offering a nuanced account of Islam’s global entanglement with consumerism, while also pointing to the challenges of addressing regional diversities and normative debates within Islamic law. It concludes that the volume serves as an essential reference for scholars of Islamic law, economics, and cultural studies, enabling them to understand how faith and the market intertwine in contemporary Muslim societies. The Routledge Handbook of Global Islam and Consumer Culture yang dieditori oleh Birgit Krawietz dan François Gauthier menghadirkan eksplorasi komprehensif tentang persinggungan antara Islam, dinamika pasar, dan praktik konsumsi dalam era global. Kontribusi interdisipliner dalam buku ini menunjukkan bagaimana nilai-nilai Islam, otoritas keagamaan, serta realitas sosial-ekonomi membentuk budaya konsumsi di berbagai konteks. Dengan menggabungkan perspektif hukum, antropologi, sosiologi, dan studi agama, buku ini membahas tema-tema penting seperti pasar halal, etika keuangan, politik identitas, dan konsumsi digital. Review ini menyoroti kekuatan buku dalam menawarkan pemahaman mendalam mengenai keterhubungan global antara Islam dan konsumerisme, sekaligus mengkritisi tantangan dalam mengakomodasi keragaman regional serta perdebatan normatif dalam hukum Islam. Disimpulkan bahwa buku ini merupakan rujukan penting bagi akademisi hukum Islam, ekonomi, dan kajian budaya untuk memahami interaksi iman dan pasar dalam masyarakat Muslim kontemporer.